Recognition of two-phase flow pattern inside evaporator tubes - Amoresano Amedeo (EDP Sciences, 2021)
The convective heat exchange mechanism in two-phase regime, can allow high exchange coefficients, as long as particular conditions are respected, in terms of vapor quality. In evaporator tubes this problem is particularly important as a deviation from the optimal flow conditions can drastically drop the efficiency of the heat exchange. This work describes an innovative methodology for identifying the different two-phase flow regimes in evaporator pipes, through the processing of the vibrational data acquired on the pipe itself. An experimental apparatus with transparent pipes has been built up to recognize flow patterns by a fast image acquisition camera. Images have been associated to vibration data acquired on pipes by accelerometer. The analysis of frequency spectrum, led to first interesting results thus it is possible to distinguish between “no bubbles” regimes and different “bubbles” regimes. A wide test campaign has been realized on vertical and horizontal pipes, simulating steam bubbles with nitrogen bubbles, reproducing the main flow patterns. The paper demonstrates the possibility to design smart and non-intrusive sensor to be applied on evaporated tubes for the recognizing of anomalous thermal flow condition and sets the stage for future engineering work.